Viability : CreateED : Strengthening Learning and Teaching Leadership in the Creative Arts Disciplines.
Thirteen case studies from the CreateED project that aimed to strengthen learning and teaching across Australian creative arts disciplines, including architecture, creative writing, design, performing arts (dance and music), and visual arts. The project facilitated those in learning and teaching leadership roles nationally to work together strategically to enhance their leadership capability, to address issues of learning and teaching importance, and to contribute publications on leadership to the scholarship of teaching and learning. The case studies relate to the theme of 'viability' and describe programs from University of Tasmania, Queensland University of Technology and Griffith University.